Estetika Bentuk Ornamen pada Nisan Raja Cakraningrat IV di Arosbaya, Bangkalan, Madura - Herman Sugianto; Sepbianti Rangga Patriani; Suparman Suparman (Lembaga Pengembangan Kinerja Dosen, 2026)
Royal burial complexes in Madura preserve visual evidence of interaction among local artistic traditions, Hindu-Buddhist visual vocabularies, and Islamic funerary culture. This study analyzes the aesthetic form of ornaments carved on the gravestone of King Cakraningrat IV in Arosbaya, Bangkalan, Madura. A descriptive qualitative case study with visual-formal analysis was applied to seven ornamental panels. Data were obtained through direct observation, photographic documentation, and literature review, then examined through motif identification, formal organization, and the aesthetic criteria of unity, complexity, and intensity. Panel 1 is dominated by stylized leaves, patran, vines, and lung motifs arranged around a strong vertical axis. Panel 2 combines a five-petaled flower with stylized foliage, while Panels 3 to 7 repeat tiered leaf and bud compositions that create a gunungan-like silhouette. Symmetry, repetition, scale gradation, and motif density produce visual coherence. The placement of mountain-like and floral forms in an Islamic grave context indicates selective cultural acculturation rather than the direct transfer of earlier religious meanings. The findings support systematic documentation, preventive conservation, and the use of local heritage in contextual art education.